The art of poetry - Valéry, Paul, 1871-1945 (Princeton University Press, 1985)
All of the major meditations on the theory and practice of poetry by one of the greatest poets of our time--and perhaps the one who has most scrupulously analyzed his art--are included in The Art of Poetry. Originally published in 1985. The Princeton Legacy Library uses the latest print-on-demand technology to again make available previously out-of-print books from the distinguished backlist of Princeton University Press. These paperback editions preserve the original texts of these important books while presenting them in durable paperback editions. The goal of the Princeton Legacy Library is to vastly increase access to the rich scholarly heritage found in the thousands of books published by Princeton University Press since its founding in 1905.
First Princeton Paperback printing.
Keywords: Poetics.; Literature -- Philosophy.; Poétique.; POETRY -- Anthologies (multiple authors); BIOGRAPHY & AUTOBIOGRAPHY -- Literary.; Literature -- Philosophy; Poetics